EFEKTIVITAS PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA DALAM MENANGGULANGI KEMISKINAN EKSTREM DI KECAMATAN CISITU KABUPATEN SUMEDANG - Amanda, Ginalia (JRPA - Journal of Regional Public Administration, 2024)
The effectiveness of the BLT-DD program is important to ensure that the expected goals are achieved as planned, namely easing the burden of living expenses of the extreme poor. This study aims to determine the effectiveness of the BLT-DD program in overcoming extreme poverty in Cisitu District, Sumedang Regency. The instruments used in this study are measuring the accuracy of program goals, program socialization, program objectives, and program monitoring. This research uses a qualitative method. The data collection techniques used are literature studies and field studies consisting of observation, interviews, and documentation. Meanwhile, the data processing procedures in this study are data reduction, data display, conclucion drawing/verification and triangulation. The technique for determining research informants, namely purposive sampling with 5 research informants. Based on the results of the study, it was concluded that the effectiveness of the BLT-DD Program in overcoming extreme poverty in Cisitu District, Sumedang Regency as a whole has not been effective enough. There are obstacles faced in the implementation of the program, including uneven targets due to lack of administrative completeness and inaccurate data, uneven distribution of information that causes a lack of public understanding, lack of understanding and education about program objectives that cause dependence so that there is ineffectiveness of program objectives, as well as in-depth and unresponsive supervision and evaluation. There are efforts to overcome these obstacles including comprehensive data collection and verification, equitable distribution of information, increased community participation, education and coaching regarding the use of assistance, as well as continuous monitoring and evaluation of programs.